Does Maimonides's Mishneh Torah forbid reading the guide of the perplexed?: on platonic punishments for freethinkers - Halper, Yehuda (AJS review, 2018)
In one passage of the Mishneh Torah, Maimonides explicitly forbids Jews from philosophical inquiry or even freethinking. This prohibition apparently includes a ban on reading or thinking about the topics of the Guide of the Perplexed. This paper argues that Maimonides's Mishneh Torah presents a consistent rejection of open philosophical inquiry. However, what is prohibited in the Mishneh Torah is not only permitted in the Guide, but the terms of the prohibition can be used as an outline of the structure of the Guide. That is to say, the Guide in a sense covers precisely the topics whose inquiry is forbidden to Jews in the Mishneh Torah. In the Mishneh Torah Maimonides does not suggest a punishment in this world for freethinkers, but in the Guide he punishes freethinkers with more study, especially metaphysical inquiry. It is possible that the Guide itself is the punishment for freethinking as defined by the Mishneh Torah. This kind of intellectual punishment has a parallel in Plato's Laws, where freethinkers are sentenced to spend five years living in the center of the city, studying physics and metaphysics with city elders.